2005
DOI: 10.1093/molbev/msi190
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Implications of an Unusual Foraminiferal β-Tubulin

Abstract: We have obtained sequence data for beta-tubulin genes from eight species of Foraminifera (forams) and alpha-tubulin sequences from four species, sampling major taxonomic groups from a wide range of environments. Analysis of the beta-tubulin sequences demonstrates that foram beta-tubulins possess the highest degree of divergence of any tubulin gene sequenced to date and represent a novel form of the protein. In contrast, foram alpha-tubulin genes resemble the conventional alpha-tubulins seen in other organisms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…Consistent with the results of those studies, α1-2 and β2 have recently been found in several species of Foraminifera (Habura et al, 2005). However, in the present study we isolated only one type of α-tubulin gene from Planoglabratella after sequencing six clones.…”
Section: Characteristics Of α-Tubulin β-Tubulin and Actin From Plansupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with the results of those studies, α1-2 and β2 have recently been found in several species of Foraminifera (Habura et al, 2005). However, in the present study we isolated only one type of α-tubulin gene from Planoglabratella after sequencing six clones.…”
Section: Characteristics Of α-Tubulin β-Tubulin and Actin From Plansupporting
confidence: 92%
“…It is widely held that microtubules are composed of two distinct polypeptides, α-tubulin and β-tubulin (Luduena et al, 1977). Therefore, it is possible that the divergent sequences of α-tubulin and β-tubulin from foraminifers result from adaptations to perform specific functions in unusual microtubule systems, as observed by Linder et al (1997) and Habura et al (2005). The results of preliminary electrophoretic and immunochemical studies have suggested that foraminiferan tubulins differ significantly from those in vertebrate cells (Koonce et al, 1986;Rupp et al, 1986).…”
Section: Aberrant Evolution Of Foraminiferan Tubulinsmentioning
confidence: 99%
“…We also add new β-tubulin data from both S. zanclea and L. setosa , confirming gene expansion in all major Radiolaria lineages, and the origin of new paralogs in the common ancestor of Retaria. The overall pattern is that the new α2-tubulin paralog presented here evolved in a similar mode to that of the β2-tubulin gene (see also Habura et al 2005; Hou et al 2013). Interestingly, none of the α2-tubulin and β2-tubulin paralogs could be identified in available Endomyxa data, suggesting that these gene duplications are synapomorphic for Retaria, with an origin after the division of Retaria and Endomyxa (fig.…”
Section: Discussionmentioning
confidence: 74%
“…These microtubule mediated pseudopods can extend and retract at a speed two orders of magnitude faster than in animal cells (Travis and Allen 1981; Bowser 2002). The extraordinary speed at which the microtubules can nucleate in Foraminifera has been linked to a duplication and neofunctionalization of β-tubulin (Habura et al 2005; Hou et al 2013). The discovery of the aberrant β2-tubulin in Retaria represented a paradox, since a corresponding α-tubulin paralog of the heterodimer could not be detected (Hou et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, sequence data for the CTD of RPB1 is not available for foraminiferans [30], partially because the 3' end of the gene appears to be divergent and is difficult to amplify. Canonical spliceosomal introns have already been identified in SSU rDNA (Habura and Bowser, unpublished), actin [31], and tubulin [32] genes in foraminiferans, indicating that the suspected alterations in the CTD of RPB1, whatever they may be, do not affect intron splicing. As described above, several contigs in the present study also contained canonical spliceosomal introns, which therefore appear to be a common feature of foraminiferal genes.…”
Section: Discussionmentioning
confidence: 99%